Дослідження функціонального стану нирок та показників метаболічних порушень у хворих на уратний нефролітіаз коморбідний з метаболічним синдромом - Білай, Сергій Іванович; Довбиш, Михайло Афанасійович; Белай, С. И.; Довбыш, М. А.; Bilai, S. I.; Dovbysh, M. A. (Полтава : [б. в.], 2019)
Хворі з метаболічним синдромом мають удвічі збільшений ризик розвитку ниркових конкрементів. При наявності всіх компонентів метаболічного синдрому частота виявлення каменів сягає 50%. У дослідження було включено 80 осіб. 1-а контрольна група хворих (n=38) на уратний нефролітіаз, яким застосовували традиційну терапію. 2-а основна група хворих (n=42) на уратний нефролітіаз коморбідний з метаболічним синдромом, які приймали традиційну терапію та загальноприйняті лікарські засоби, які корегують метаболічні порушення. Застосування спільно з традиційною терапією лікарських засобів, що впливають на метаболічні процеси, диференційовано урикостатичних і уриколітичних засобів у хворих уратним нефролітіазом коморбідним з метаболічним синдромом сприяло нормалізації показників функціонального стану нирок та метаболічних порушень. Больные с метаболическим синдромом имеют вдвое больший риск развития почечных конкрементов. При наличии всех компонентов метаболического синдрома частота выявления камней достигает 50%. В исследование было включено 80 человек. Первая контрольная группа больных (n = 38) уратным нефролитиазом, которые принимали традиционную терапию. Вторая основная группа больных (n = 42), которые страдали уратным нефролитиазом коморбидным с метаболическим синдромом, принимали традиционную терапию и общепринятые лекарственные средства, которые корректируют метаболические нарушения. Применение совместно с традиционной терапией лекарственных средств, влияющих на метаболические процессы, дифференцированно урикостатических и уриколитических средств у больных уратным нефролитиазом коморбидным с метаболическим синдромом способствовало нормализации показателей функционального состояния почек и метаболических нарушений. Urolithiasis is one of the most common urological diseases. Urolithiasis affects 9.6% of the population of the planet, and among all diseases of the urological profile, urolithiasis reaches 40%. Like urolithiasis, the prevalence of metabolic syndrome increases and in modern society it affects up to 39% of the adult population of the planet, and in people over 60, its frequency is found to be 42-43.5%. Patients with metabolic syndrome have a doubly increased risk of renal excrement. In the presence of all components of the metabolic syndrome, the detection rate of stones reaches 50%. In this regard, the diagnosis and correction of the treatment of urolithiasis combined with metabolic syndrome is a topical issue in urology, a necessary condition and an important part of the algorithm for metaphylactic of urolithiasis. The purpose of this study is to investigate the changes in the functional state of the kidneys and upper urinary tract, the indicators of metabolic disorders in patients with nephrolithiasis combined with metabolic disorders during complex traditional therapy. Object and methods of the study. The study included 80 patients. The groups of patients were divided depending on the type of the drug treatment to the main and control groups. For normal indicators, indicators were received from healthy individuals (donors). 1-st control group of patients (n = 38) for nephrolithiasis, which was used traditional therapy: anticholinergic agent, nonsteroidal anti-inflammatory agent, Uralite U, water stroke. The 2nd main group of patients (n = 42) for nephrolithiasis comorbid with metabolic syndrome, who received traditional therapy and commonly used drugs that regulate metabolic disorders. To study the condition of patients, research carried out using anamnestic, clinical, laboratory, radiological, ultrasound and biochemical methods. The study of the indicators was carried out: before treatment, 7 days, 14 days, in 1,5-2 months, in 3-6 months. Results and their discussion. Patients in the control and main group with urolithiasis, comorbid with the metabolic syndrome before treatment, there was an increase in the level of creatinine and urea in comparison with the group of healthy persons, as well as a decrease in the velocity of glomerular filtration, indicating deterioration of the functional state of the kidneys. Moreover, the level of these indicators was somewhat higher in the main group due to metabolic disorders. Patients with nephrolithiasis, comorbid with metabolic syndrome significantly increased the levels of CH, TG, β-LP, LDL cholesterol, VLDL cholesterol, and reduced HDL cholesterol compared with healthy individuals. The level of glucose and glycosylated hemoglobin also significantly increased in patients with urolithiasis with metabolic disorders. In the process of treatment in patients with control and major groups, there was an ambiguous change in the parameters of the functional state of the kidneys, lipid and carbohydrate metabolism. Thus, patients with nephrolithiasis showed a slight increase in the level of creatinine and urea, as well as the content of cholesterol, β-LP. A moderate increase in TG, LDL cholesterol, VLDL cholesterol and a slight decrease in HDL cholesterol for 6 months of follow-up noted in patients in the control group. Conclusions. Apparently, changes in the parameters of the functional state of the kidneys and lipid metabolism are primarily due to disturbances of purine metabolism, which accompanied by hyperuricemia and hyperuricuria.
Исследование функционального состояния почек и показателей метаболических нарушений у больных уратным нефролитиазом коморбидным с метаболическим синдромом
Research of functional state of kidneys and indicators of metabolic disorders in patients with nephrolitiasis in combination with metabolic syndrome
Keywords: уратний нефролітіаз; метаболічний синдром; уратный нефролитиаз; метаболический синдром; urolithiasis; metabolic syndrome